(untitled) (Solukhumbu Multiple Campus Research Journal, 2024)
Effective working capital management (WCM) is crucial for assessing an organization’s performance. An optimal WCM approach is expected to enhance profitability and contribute to overall company value. This study also examines the influence of working capital policy alongside control variables such as business growth, firm size, and debt on profitability. This research aims to investigate the relationship between working capital policies and business profitability within three public cement industries in Nepal: Hetauda Cement Limited, Shivam Cement Limited, and Udayapur Cement Limited. The profitability of the selected firms is measured using market and accounting metrics, specifically Net Operating Profitability (NOP), Return on Equity (ROE), and Return on Assets (ROA). The study employs the Ordinary Least Squares (OLS) regression method to evaluate the research hypothesis. Data is collected from the Nepal Stock Exchange for the period between 2011 and 2020.The results indicate that working capital policies have a significant negative impact on the profitability of the firms studied. The findings underscore the importance of effective working capital management in enhancing profitability within Nepal’s cement industry, suggesting that firms must optimize their working capital policies to improve financial performance.